Digital Marketing and Branding: Strategies for Improving the Quality and Marketing of Tofu Factory UMKM Products in Sukajati Village - M. Aksel Prima; Nesa Fitriyani Hasanah (Aimmah: Social Sciences Journal, 2025)
Developing village potential towards a progressive society requires creativity in solving local economic problems. Sukajati Village has significant potential for UMKM, one of which is the Pak Agung Tofu Factory. However, limited knowledge regarding visual identity and digital marketing is a major obstacle to expanding market reach. This article aims to describe the implementation of a community service program through digital marketing and branding assistance. The methods used were field observation and direct assistance (a participatory approach). The results of the activity indicate that creating a logo as a product identity, optimizing social media, and registering a location on Google Maps can improve the visual appeal and accessibility of the business. This program successfully provided UMKM with a new understanding of the importance of modern marketing strategies in the digital era.